2015
DOI: 10.1007/s00281-015-0519-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of resident microglia and infiltrating monocytes in murine CNS autoimmunity

Abstract: Macrophages can be of dual origin. Most tissue-resident macrophage compartments are generated before birth and subsequently maintain themselves independently from each other locally in healthy tissue. Under inflammatory conditions, these cells can however be complemented by macrophages derived from acute monocyte infiltrates. Due to the lack of suitable experimental systems, differential functional contributions of central nervous system (CNS)-resident microglia and monocyte-derived macrophages (MoMF) to CNS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 135 publications
(179 reference statements)
2
52
0
Order By: Relevance
“…Cd11b is an integral membrane-associated protein that is a cellular marker of CNS microglia; however, Cd11b is also present on the surface of other monocyte-derived lineages, including macrophages. Macrophages are capable of invading the CNS, sparking neuroinflammation and neurodegeneration (Shemer and Jung, 2015). MGM15, MGM3, and MGM13 were further assessed for unintended non-microglial cellular gene expression arising from Cd11b+ enrichment.…”
Section: 3 Results and Discussionmentioning
confidence: 99%
“…Cd11b is an integral membrane-associated protein that is a cellular marker of CNS microglia; however, Cd11b is also present on the surface of other monocyte-derived lineages, including macrophages. Macrophages are capable of invading the CNS, sparking neuroinflammation and neurodegeneration (Shemer and Jung, 2015). MGM15, MGM3, and MGM13 were further assessed for unintended non-microglial cellular gene expression arising from Cd11b+ enrichment.…”
Section: 3 Results and Discussionmentioning
confidence: 99%
“…The importance of developing methods to distinguish microglia from hematopoietic myeloid cells becomes increasingly clear, with an ever-increasing number of studies revealing differential roles of these monocytic cells in various CNS diseases (33,34). Differential functions of microglial cells can be partially attributed to their unique origin from yolk sac progenitors (29) and the fact that they can maintain themselves by virtue of longevity and self-renewal (29,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from our lab have addressed this void by cell-specific gene targeting approaches, demonstrating that oligodendroglial TNFR2 promotes oligodendrocyte differentiation and remyelination in experimental autoimmune encephalomyelitis (EAE), a model of MS (Madsen PM, 2016). Microglia and monocytes/macrophages (Mo/MΦ) play critical roles in MS and EAE (Shemer and Jung, 2015), and both express TNFR2 (Brambilla et al, 2011). However, the current knowledge of TNFR2 function in these populations is limited to only two in vitro studies: in microglia, TNFR2 was shown to promote the expression of antiinflammatory and neuroprotective genes (Veroni et al, 2010), and in macrophages to play an auxiliary role in activating proinflammatory TNFR1 signaling (Ruspi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%